2017
DOI: 10.21125/inted.2017.1269
|View full text |Cite
|
Sign up to set email alerts
|

Learner Satisfaction and Knowledge Construction in Blended Learning

Abstract: This study investigates differences in instructional and learner factors between two groups of learners exposed to online only and blended delivery formats, respectively, in an effort to compare learning outcomes and other instructional variables between online and blended delivery methods. Findings indicated that no significant differences existed in learning outcomes; however, significant differences existed in several instructional and learner factors between the two delivery format groups. Discussions abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In terms of the positive influence of STUD on SAST, the results show that encouraging student-to-student dialogue may improve learner satisfaction (Kintu et al, 2017b). One of the biggest barriers to online learning is students' lack of intimacy and interaction.…”
Section: Discussionmentioning
confidence: 92%
“…In terms of the positive influence of STUD on SAST, the results show that encouraging student-to-student dialogue may improve learner satisfaction (Kintu et al, 2017b). One of the biggest barriers to online learning is students' lack of intimacy and interaction.…”
Section: Discussionmentioning
confidence: 92%
“…The results of some research studies show that students's satisfaction in the online learning system is high because they can interact and work together with their friends through this system. They can also reflect the characteristics and quality of learning during the blended learning system [11]. In other studies, however, student learning satisfaction has differed levels depending on their learning styles and backgrounds.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A similar result has been found in other studies claiming that without a teacher, students might lose their attention or ignore the tasks easily (Moore & Kearsely, 2011). For this reason, as it is suggested in a Kintu, Zhu, and Kagambe (2017) study that teachers should have concern about the connectedness issue by providing balance interaction between teachers, students, and peers when using this delivery method. Similar to the findings in this study it was also found that students wanted more interactive activities in online mode such as real-time chatting or video call, where they could see their friends or the teacher.…”
Section: Perceptions Towards Blended-learning Environment and Its Eff...mentioning
confidence: 99%